New amino acid esters of salicylanilides active against MDR-TB and other microbes - Krátký, Martin; Vinšová, Jarmila; Buchta, Vladimír; Horvati, Kata; Bösze, Szilvia; Stolaříková, Jiřina (European journal of medicinal chemistry, 2010)
Eleven halogenated (S)-2-(phenylcarbamoyl)phenyl 2-acetamido-3-phenylpropanoates (3a-3k) were designed and synthesized as potential antimicrobial agents. They were evaluated in vitro against some mycobacterial, bacterial and fungal strains. These compounds were active against drug-sensitive and atypical mycobacterial strains with general MIC values from 0.25 to 16 μmol/L. The most active compounds were (S)-4-chloro-2-(4-(trifluoromethyl)phenylcarbamoyl)phenyl 2-acetamido-3-phenylpropanoate (3i) and (S)-4-bromo-2-(4-(trifluoromethyl)phenylcarbamoyl)phenyl 2-acetamido-3-phenylpropanoate (3k) which exhibited activity against MDR and XDR-TB strains with MICs from 1 to 2 μmol/L. 3k was shown to be less cytotoxic with higher IC50. Some compounds exhibited low MICs on Gram-positive bacteria (MICs≥0.98 μmol/L) and on fungi (MICs≥3.9 μmol/L).
Keywords: houby; Tuberculosis, Multidrug-Resistant; Dose-Response Relationship, Drug; Salicylanilides; vztah mezi dávkou a účinkem léčiva; salicylanilidy; estery; Anti-Bacterial Agents; Bacteria; Stereoisomerism; extenzivně rezistentní tuberkulóza; Antifungal Agents; multirezistentní tuberkulóza; Microbial Sensitivity Tests; Fungi; stereoizomerie; vztahy mezi strukturou a aktivitou; racionální návrh léčiv; antibakteriální látky; molekulární struktura; Esters; Amino Acids; Extensively Drug-Resistant Tuberculosis; Drug Design; mikrobiální testy citlivosti; aminokyseliny; Structure-Activity Relationship; antifungální látky; Molecular Structure